Source area evolution and thermal record of an Early Cretaceous back-arc basin along the northwesternmost Colombian Andes. (October 2019) - León, S.; Cardona, A.; Mejía, D.; Botello, G.E.; Villa, V.; Collo, G.; Valencia, V.; Zapata, S.; Avellaneda-Jiménez, D.S.
Abstract: Identifying the provenance signature and geodynamic setting on which sedimentary basins at convergent margins grow is challenging since they result from coupled erosional and tectonic processes, which shape the evolution of source areas and the stress regime. The Early Cretaceous evolution of the northern Andes of Colombia is characterized by extensional tectonics and the subsequent formation of a marginal basin. The Abejorral Formation and coeval volcano-sedimentary rocks are exposed along the western flank and axis of the Central Cordillera. They comprise an Early Cretaceous transgressive sequence initially accumulated in fluvial deltaic environments, which switched towards a deep-marine setting, and are interpreted as the infilling record of a marginal back-arc basin. Available provenance data suggest that Permian-Triassic metamorphic and less abundant Jurassic magmatic rocks forming the basement of the Central Cordillera sourced the Abejorral Formation. New detailed volcanic and metamorphic lithics analyses, conventional and varietal study of heavy minerals, detrital rutile mineral chemistry, allowed us to document changes in the source areas defined by the progressive appearance of both higher-grade and more distal low-grade metamorphic sources, which switched from pelitic to dominantly mafic in composition. Crystallochemical indexes of clay minerals of fine-grained rocks of the Abejorral Formation suggest that samples located close to the Romeral Fault System show characteristics of low-medium P-T low-grade metamorphism, whereas rocks located farther to the northeast preserve primary diagenetic features, which suggest a high heat-flow accumulation setting. We interpret that the Abejorral Formation records the progressive unroofing of the Central Cordillera basement that was being rapidly exhumed, as well as the incorporation of distal subduction-related metamorphic complexes to the west in response either to the widening of extensional front or the reactivation of fault structures on the oceanward margin of the basin. Although the deformational record of the Abejorral Formation would have resulted from over-imposed episodes, our new geochronological constraints suggest that this sedimentary sequence must have been deformed before the Paleocene due to the presence of arc-related intrusive non-deformed magmatic rocks with a crystallization age of ca. 60 Ma. Highlights: Multi-proxy provenance of Early Cretaceous rocks of the Central Cordillera, Colombia. Unroofing patterns and variations of the source areas. Low-medium-pressure and high heat-flow during back-arc basin filling. Arc-related magmatism at ca. 60 Ma sealed early history of basin deformation.